2021
DOI: 10.1016/j.tcb.2020.11.008
|View full text |Cite
|
Sign up to set email alerts
|

The Ways of Actin: Why Tunneling Nanotubes Are Unique Cell Protrusions

Abstract: Actin remodeling is at the heart of the cell' response to external or internal stimuli allowing a variety of membrane protrusions to form. Fifteen years ago, tunneling nanotubes (TNTs) were identified, bringing a novel addition to the family of actin-supported cellular protrusions. Their unique property as conduits for cargo transfer between distant cells, emphasizes the unique nature of TNTs among other protrusions. While TNTs in different pathological and physiological scenarios have been described, the mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(83 citation statements)
references
References 91 publications
3
78
0
Order By: Relevance
“…The characterization of TNTs in vitro indicated that TNTs are uniformly F-actinpositive [30], which separates them from other cellular protrusions such as tethers and nanopodia [5]. Surprisingly, F-actin may not be simply arranged in TNTs, as we thought until Anna Sartori-Rupp et al demonstrated highly organized parallel actin bundles within TNTs [3].…”
Section: Difference In Morphologymentioning
confidence: 77%
See 2 more Smart Citations
“…The characterization of TNTs in vitro indicated that TNTs are uniformly F-actinpositive [30], which separates them from other cellular protrusions such as tethers and nanopodia [5]. Surprisingly, F-actin may not be simply arranged in TNTs, as we thought until Anna Sartori-Rupp et al demonstrated highly organized parallel actin bundles within TNTs [3].…”
Section: Difference In Morphologymentioning
confidence: 77%
“…Paradoxically, TNTs were also observed in M-sec or p53-deficient cells [42,47]. Such inconsistent results imply that the biogenesis of TNTs may not have a universal molecular regulation mechanism, probably due to their heterogeneity [30].…”
Section: Different Mechanisms Of Tnts Formationmentioning
confidence: 98%
See 1 more Smart Citation
“…Membrane depolarization at the leading edge of wounds has been shown to connect adjacent cells via TNTs activation of PI3 kinase signaling suggesting a supportive role of TNTs in wound healing, which involves F-actin remodeling (118). Similarly, TNT formation and induction have also been observed following injury, trauma or chronic tissue stresses (38).…”
Section: Tnts -In Vivo Significance and Challengesmentioning
confidence: 99%
“…The discovery 16 years ago that thin and very long membrane tubes can interconnect individual cells has broadened our understanding of how normal and malignant tissues function [1][2][3][4]. In effect, these protrusions allow cells to convene to a communicating syncytial network that is capable of exchange of information, molecules, and partially even cell organelles in a complex and multitude manner [3,5].…”
mentioning
confidence: 99%